2012
DOI: 10.1088/0953-4075/45/8/085402
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis on optical limiting performance of a series of phthalocyanines for nanosecond pulses

Abstract: The optical limiting properties of a series of peripherally substituted phthalocyanines with different central metals and axial chloride ligand for nanosecond pulses have been studied by solving numerically the two-dimensional paraxial field equation together with the rate equations using the Crank-Nicholson method. It is shown that all of these compounds exhibit good optical limiting behaviour, and phthalocyanines with heavier central metals have better optical limiting performance due to the faster intersyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In most OL materials, ESA is established on a triplet state. Electrons are first promoted to a singlet state by directly absorbing incident photons and then populating the triplet state via intersystem crossing (ISC). However, this process introduces two disadvantages: first, linear transmittance is relatively low because OL materials are required to work in a resonant absorption band to activate ESA; second, the typical ISC times in OL materials range from picoseconds to several nanoseconds, which limits the response time toward ultrafast pulses. To overcome these disadvantages and achieve ultrafast broad-band OL, two-photon absorption (TPA) induced ESA (TPA–ESA) based on the singlet state is employed.…”
Section: Introductionmentioning
confidence: 99%
“…In most OL materials, ESA is established on a triplet state. Electrons are first promoted to a singlet state by directly absorbing incident photons and then populating the triplet state via intersystem crossing (ISC). However, this process introduces two disadvantages: first, linear transmittance is relatively low because OL materials are required to work in a resonant absorption band to activate ESA; second, the typical ISC times in OL materials range from picoseconds to several nanoseconds, which limits the response time toward ultrafast pulses. To overcome these disadvantages and achieve ultrafast broad-band OL, two-photon absorption (TPA) induced ESA (TPA–ESA) based on the singlet state is employed.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that different central metals have different influences on the OL behavior. Graphene oxide-metal free porphyrin owns the best nonlinear absorption behavior compared with the others, while previous studies showed that porphyrin with heavier central metal has better OL performance as a result of the faster ISC caused by the enhanced spin-orbit coupling [25]. In the composite, graphene oxide acts as electron acceptor, and peripheral porphyrin shows as electron donor.…”
Section: Resultsmentioning
confidence: 93%
“…Optical power limiting occurs when the absolute transmittance of a material decreases as the intensity of the input laser field increases beyond a critical value; indeed, an optical power limiter exhibits a high and linear transmission (at least of 70 ) below a certain threshold, to preserve the detection function of sensors, but above which the optical nonlinear properties of the material limit the transmission of light. Desirable properties for power limiting applications can include a high linear transmittance, a broad spectral response, and a low limiting threshold 4 . Noting that the limiting threshold is defined as the incident intensity at which the transmittance falls to 50 of the linear transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the widespread use of intense lasers in various fields such as the scientific, industrial, medical therapy and military sectors, the power limiting becomes an important research branch in nonlinear optical processes; materials possessing large optical nonlinearities have been potentially employed in a number of applications in limiting devices and extensive theoretical and experimental investigations on power limiting, based on optical nonlinear processes, have been reported 7 12 . One of the mechanisms that may lead to a nonlinear absorption effect is reverse saturable absorption (RSA), also referred to as excited-state or two-photon absorption, in which the absorption cross section from excited-state energy levels is significantly higher than the ground-state absorption cross section 4 , 8 , 13 ; in fact, RSA, being one of the major OL mechanism, has been reported for applications in efficient OLs 14 – 20 , with compounds such as organic and inorganic materials 21 , 22 , liquid crystal 23 , nanocomposites 24 , nanoparticles 25 and thin film 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation